The inflammatory cytokine TNF‐α regulates the biological behavior of rat nucleus pulposus mesenchymal stem cells through the NF‐κB signaling pathway in vitro. Issue 8 (2nd April 2019) - Cheng, Shi; Li, Xiaochuan; Jia, Zhiwei; Lin, Linghan; Ying, Jinwei; Wen, Tianyong; Zhao, Yachao; Guo, Ziming; Zhao, Xiyan; Li, Dandan; Ji, Wei; Wang, Deli; et al.
Abstract: Nucleus pulposus (NP) mesenchymal stem cells (NPMSCs) are a potential cell source for intervertebral disc (IVD) regeneration; however, little is known about their response to tumor necrosis factor‐α (TNF‐α), a critical inflammation factor contributing to accelerating IVD degeneration. Accordingly, the aim of this study was to investigate the regulatory effects of TNF‐α at high and low concentrations on the biological behaviors of healthy rat NPMSCs, including proliferation, migration, and NP differentiation. In this study, NPMSCs were treated with different concentration of TNF‐α (0‐200 ng/mL). Then we used annexin V/propidium iodide flow cytometry analysis to detect the apoptosis rate of NPMSCs. Cell Counting Kit‐8, Edu assay, and cell cycle test were used to examine the proliferation of NPMSCs. Migration ability of NPMSCs was detected by wound healing assay and transwell migration assay. Pellets method was used to induce NP differentiation of NPMSCs, and immunohistochemical staining, real‐time polymerase chain reaction, and Western blot analysis were used to examine the NPC phenotypic genes and proteins. The cells were further treated with the nuclear factor‐κB (NF‐κB) pathway inhibitor Bay 11‐7082 to determine the role of the NF‐κB pathway in the mechanism underlying the differentiation process. Results showed that treatment with a high concentration of TNF‐α (50‐200 ng/mL) could induce apoptosis of NPMSCs, whereas a relatively low TNF‐α concentration (0.1‐10 ng/mL) promoted the proliferation and migration of NPMSCs, but inhibited their differentiation toward NP cells. Moreover, we identified that the NF‐κB signaling pathway is activated during the TNF‐α‐inhibited differentiation of NPMSCs, and the NF‐κB signal inhibitor Bay 11‐7082 could partially eliminate the adverse effect of TNF‐α on the differentiation of NPMSCs. Therefore, our findings provide important insight into the dynamic biological behavior reactivity of NPMSCs to TNF‐α during IVD degeneration process, thus may help us understanding the underlying mechanism of IVD degeneration. Graphical Abstract: A high concentration of tumor necrosis factor‐α (TNF‐α; 50‐200 ng/mL) could induce apoptosis of nucleus pulposus (NP) mesenchymal stem cells (NPMSCs), whereas a relatively low TNF‐α concentration (0.1‐10 ng/mL) promoted the proliferation and migration of NPMSCs, but inhibited their differentiation toward NP cells through NF‐kB signaling pathway.